A Long Journey of Lithium: From the Big Bang to Our Smartphones. Issue 4 (19th December 2019) - Xu, Kang
Abstract : Lithium was nucleosynthesized in the first 5 min of The Big Bang around 13.7 billion years ago, together with hydrogen and helium. It is the very first metal in the period table (atomic number 3), the lightest metal (density 0.534 g cm −3 ), and the metal with the lowest electrochemical potential (−3.04 V vs standard hydrogen electrode). All these characteristics fortuitously combine to make Li the most power anode material for energy storage.